2006
DOI: 10.1590/s0100-46702006000300002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structure and vibrational spectra of glucose and fructose

Abstract: Molecular modelling using semiempirical methods AM1, PM3, PM5 and, MINDO as well as the Density Functional Theory method BLYP/DZVP respectively were used to calculate the structure and vibrational spectra of d-glucose and d-fructose in their open chain, α-anomer and β-anomer monohydrate forms. The calculated data show that both molecules are not linear; ground state and the number for the point-group C is equal to 1. Generally, the results indicate that there are similarities in bond lengths and vibrational mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
137
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(153 citation statements)
references
References 23 publications
10
137
0
1
Order By: Relevance
“…They found that both molecules are not linear and show similarities in bond lengths and vibrational modes. The bond lengths for fructose and glucose calculated by Ibrahim et al [30], given in Table 1, agree with the present work.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…They found that both molecules are not linear and show similarities in bond lengths and vibrational modes. The bond lengths for fructose and glucose calculated by Ibrahim et al [30], given in Table 1, agree with the present work.…”
Section: Resultssupporting
confidence: 92%
“…The optimized molecular structures of these compounds are given in Scheme 1. The geometrical parameters for the fructose and glucose (Scheme 1) indicate that there are similarities in the structure which is in agreement with recent work on the analysis of the structure and vibrational spectra of the glucose and fructose by Ibrahim et al [30], using BLYP/DZVP level. They found that both molecules are not linear and show similarities in bond lengths and vibrational modes.…”
Section: Resultssupporting
confidence: 90%
“…It may suggest that properties of inulin dominate these of other components of the DRB. Because there is a total lack of the assignment for spectra of inulin, specification of the fingerprint peaks was made with the help of the published data for sucrose, i.e., the simple disaccharide composed of glucose and fructose linked via their anomeric carbons (Max 2007;Adina 2010), glucose, and fructose (Ibrahim 2006). The authors have shown that vibrations within the carbohydrate molecules show characteristic frequencies in the spectral region from 600 to 1500 cm -1 in which C-O and C-C group vibration modes are present.…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…Modeling techniques help in a better way to understand the physical properties of fullerenes and its derivatives. In the literature ab initio calculations have been used to study the structural and electronic properties of small silicon clusters as well as endohedral metallofullerenes (Andreoni 1993;Ibrahim et al 2006). Ab initio calculations on the stability of MC 60 (M = Sc, Y and K) and Si atom-doped endohedral C 60 have been reported in the literature (Misra et al 2012: Suzuki et al 1994Ibrahimand El-Haes 2005;Lu et al 2001).…”
Section: Introductionmentioning
confidence: 99%